Design and fabrication of go-kart front suspension system - Syahriza, Muhammad Irfan; Mohd Yusof, Ab Aziz (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
The suspension system is a crucial component of an automotive vehicle, ensuring smooth rides by absorbing shocks while maintaining handling performance and keeping all tires in contact with the road. This project focuses on developing a functional front suspension for a go-kart, selecting the most suitable type to integrate into its frame. Through mock-ups and testing of different suspension types, an optimal choice will be determined. Comprehensive research and evaluation will contribute to enhancing the go-kart's overall performance and ride quality.